Morphological and mating behavioral characteristics polled Bali cattle. Issue 1 (April 2020) - Zulkharnaim,; Baco, S; Yusuf, M; Rahim, L
Abstract: This research aimed to identify morphological characteristics Bali polled cattle and to know the mating behavioral characteristics of Bali polled male. Morphological characteristics research used 100 head samples, including 11 head of polled cattle and 89 head of horned cattle. Identification of morphological characteristics using t-test independent sample using analysis Completely Randomized Design. Mating behavioral characteristics research used 5 head samples, including 3 head of polled cattle and 2 head of horned cattle. Mating behavioral characteristics were analyzed by several parameters: the first time teasing a teaser (second), when flehmen arise (second) and frequency or number of flehmen (times)The results showed that the morphological characteristics Bali polled cattle were not significantly different with Bali horned. The mating behavioral characteristics of Bali polled cattle were not significantly different with Bali horned.